2010
DOI: 10.1007/s11746-010-1554-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Biodiesel by Transesterification of Rapeseed Oil with Methanol Using Solid Base Catalyst Calcined K2CO3/γ‐Al2O3

Abstract: We report here the preparation of biodiesel by transesterification of rapeseed oil with methanol using calcined K 2 CO 3 /c-Al 2 O 3 as a solid base catalyst. The prepared catalysts were characterized using SEM, IR and BET, and their catalytic activities were evaluated. The reaction conditions were optimized, and in particular, the conversion can be as high as 98.62% under the optimal reaction conditions. In addition, the effect of the presence of water in the reaction system on the catalytic activity was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
13
0
4
Order By: Relevance
“…However, it was observed that at molar ratios above 4/1, excessive methanol had no significant effect on the yield. Conversely, a longer time was required for the subsequent separation stage because separation of the esters layer from glycerol was difficult due to the fact that methanol with one polar hydroxyl group could emulsify the products [29]. Hence, the best methanol/oil molar ratio was selected as 4/1.…”
Section: Transesterification Reactionmentioning
confidence: 99%
“…However, it was observed that at molar ratios above 4/1, excessive methanol had no significant effect on the yield. Conversely, a longer time was required for the subsequent separation stage because separation of the esters layer from glycerol was difficult due to the fact that methanol with one polar hydroxyl group could emulsify the products [29]. Hence, the best methanol/oil molar ratio was selected as 4/1.…”
Section: Transesterification Reactionmentioning
confidence: 99%
“…More recently, there has been an increasing development of solid base catalysts, such as NaOH, KOH, KNO 3 , K 2 CO 3 , KI, and KF supported on alumina and zeolites [19][20][21][22][23][24]. The KOH/ bentonite catalyst was used for the transesterification of palm oil to biodiesel by Soetaredjo et al [20].…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel has higher cetane number than petroleum diesel, biodegradable, contains no sulphur and aromatic compounds and resulting in lower emissions than petroleum diesel [1][2][3][4]. Various methods have been employed for biodiesel production, both conventional [5][6][7][8], enzymatic [9][10][11], or even advanced technologies [12][13][14][15][16] methods. Conventionally, biodiesel was produced by homogeneous and heterogeneous catalysts, either acid or base catalysts as previously found [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been employed for biodiesel production, both conventional [5][6][7][8], enzymatic [9][10][11], or even advanced technologies [12][13][14][15][16] methods. Conventionally, biodiesel was produced by homogeneous and heterogeneous catalysts, either acid or base catalysts as previously found [5][6][7][8]. However, transesterification reaction using homogeneous catalysts are constrained by the complexity of the purification and separation steps [17,18].…”
Section: Introductionmentioning
confidence: 99%